Public policies and food systems in Latin America - Le Coq, Jean-François; Grisa, Catia; Guéneau, Stéphane; Niederle, Paulo (éditions Quae, 2022)
Food problems are the order of the day. Solving the problems of hunger and malnutrition, producing and guaranteeing access to healthy food, preserving the environment, valuing local cultures and ensuring citizen participation are some of the many challenges that permeate the dynamics of food systems. This book addresses the role of Latin American public policies and actions in the configuration of healthy and sustainable food systems. Written by scholars specialized in various disciplines (economy, sociology, policy science, etc.) and hailing from ten Latin American countries, it provides a historical overview of national food policies, examines recent policy changes and explores innovative urban and rural experiences at local level. The authors also discuss the challenges of developing specific policy objectives related to sustainable food systems. This book shows how référentiels for public food policies have become more integrated in Latin America and takes a closer look at several promising local initiatives. However, it also highlights the many constraints in fostering sustainable food systems in the region, such as persistent competition among production models, land tenure inequalities and coordination issues among actors and state bodies. It will be of interest to a scientific audience of teachers and food systems professionals, as well as any readers interested in policy dynamics in Latin America.